The effect of the performance of the audit committee, internal audit, and manager religion on the implementation of good corporate governance and their implications on fraud - Rita Friyani; Haryadi Haryadi; Afrizal Afrizal; Enggar Diah Puspa Arum (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2022)
The main objective of this research is to analyze the performance of the audit committee, internal audit, and religiosity of the manager on the implementation of good corporate governance (GCG) and its implication for fraud. The study was conducted at State-owned enterprises (SOEs) in Indonesia. The population of this research is all SOEs in Indonesia, and the number of samples is 89 SOEs (based on the Slovin formula). The sampling method used a simple random sampling technique. The research data was obtained by submitting a list of questions to the selected respondents. Respondents consist of the chairman of the audit committee or members of the audit committee, the head of internal audit or members of internal audit, the corporate secretary, and the finance director (financial manager). The data were analyzed using the SEM-PLS model. The research proves that the performance of audit committees and internal audits affects the implementation of GCG, while the religiosity of managers does not affect the implementation of GCG. The research also proves that the performance of the audit committee and the implementation of GCG affect fraud, while internal audit and religiosity of managers do not affect fraud